1997
DOI: 10.1097/00005792-199703000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Diffuse Idiopathic Skeletal Hyperostosis Clinical Features and Functional Status

Abstract: Diffuse idiopathic skeletal hyperostosis (DISH) is a common but little-studied disorder in the elderly that is infrequently recognized by physicians. Its prevalence in adults over 40 years of age is estimated at 3.8% for men and 2.6% for women. The present case-control study evaluated the history of pain and stiffness, radicular pain and enthesitis, physical findings on the musculoskeletal examination, and level of physical and psychologic disability in 130 persons: 56 patients with DISH, 43 control patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
1
13

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 54 publications
7
85
1
13
Order By: Relevance
“…Back pain, usually lasting for >3 months, was present in nearly all patients of this study. This finding is in line with previous data suggesting that DISH, which was first described as a radiologic state, could be associated with spinal symptoms such as pain or stiffness, which could be worse than for patients with spondylosis (29). The substantial proportion of patients reporting axial SpA-like symptoms in this study illustrates the potential issue for the clinician to discriminate between these 2 diseases, which may share common clinical features such as postural abnormalities (15).…”
Section: Discussionsupporting
confidence: 91%
“…Back pain, usually lasting for >3 months, was present in nearly all patients of this study. This finding is in line with previous data suggesting that DISH, which was first described as a radiologic state, could be associated with spinal symptoms such as pain or stiffness, which could be worse than for patients with spondylosis (29). The substantial proportion of patients reporting axial SpA-like symptoms in this study illustrates the potential issue for the clinician to discriminate between these 2 diseases, which may share common clinical features such as postural abnormalities (15).…”
Section: Discussionsupporting
confidence: 91%
“…There have been few systematic studies of the clinical consequences of DISH (5). One of the first reported studies on this condition showed that stiffness and mild middle-to-low back pain were found in 80% of patients, dysphagia was present in 28%, elbow pain in 13%, and heel problems in 23% (6).…”
mentioning
confidence: 99%
“…Various metabolic, endocrinological, genetic, and environmental factors have been postulated but none has generally been agreed upon (Mata et al 1997;Li et al 2007). DISH is often linked to obesity (Forestier & Rotes-Querol 1950;Resnick & Niwayama 1976;Utsinger 1985;Denko et al 1994;Vezyroglou et al 1996;Mata et al 1997;el Miedany et al 2000;Belanger & Rowe 2001;Kiss et al 2002a;Mader et al 2005).…”
Section: Treatmentmentioning
confidence: 99%
“…Some authors suggested that hyperglycemia was the most useful laboratory abnormality concurrent with DISH (Utsinger 1985). Others found no significant difference in glucose levels between patients with and without DISH (Denko et al 1994;Mata et al 1997). The relationship with type 2 DM (or non-insulin dependent DM) and DISH was often postulated, but remains controversial (Kiss et al 2002a;Sarzi-Puttini & Atzeni 2004;Li et al 2007).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation